Nicaragua : Requests for Purchase under the Rapid Financing Instrument and Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Nicaragua. (IMF Staff Country Reports; Country Report, 2020)
Nicaragua faces an acute crisis as the COVID-19 shock comes on top of a two- year recession. So far, the speed of transmission of the pandemic in Nicaragua, in terms of officially confirmed cases, has been slower than in neighboring countries, but this may understate the true spread of the disease. The pandemic is expected to produce the third year of consecutive recession and lead to large fiscal and external financing needs given the impact of voluntary distancing and regional and global spillovers. The very limited fiscal space, eroded by the ongoing recession and the limited external financing, constrains the authorities' ability to self-finance the emergency response.